1995
DOI: 10.1016/s1078-5884(05)80112-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of contralateral carotid stenosis and occlusion on cerebral oxygen saturation during carotid artery surgery

Abstract: The greatest changes in CsO2 occurred in the operated side cerebral hemispheres in those with a contralateral carotid artery occlusion. However, a contralateral carotid artery occlusion does not reliably predict the need for a shunt and cerebral monitoring remains essential; although is only required on the operated side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 17 publications
0
15
0
4
Order By: Relevance
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…20 Thus, NIRS allows real-time changes in CBO and rCBF to be characterized continuously, al-though it does not measure baseline rCBF. Near-infrared spectroscopy has been used to monitor changes in hemodynamic status, which have been induced by a variety of neurosurgical procedures and functional tasks that cause both decreases 1,6,7,9,[11][12][13]15,18,[27][28][29]31,32,46,47,52 and increases 8,19,21,40,[42][43][44][45] in rCBF. Simultaneous measurements conducted using NIRS and PET scanning have demonstrated that the hemodynamic status estimated with NIRS was consistent with PET results.…”
mentioning
confidence: 99%
“…The cerebral oximeter used in our study has already compared favorably with other valid techniques such as transcranial Doppler imaging, electroencephalography (EEG), and evaluation of somatosensory evoked potentials (SSEPs) for determining cerebral malperfusion. Williams and colleagues (16) have demonstrated that there is a good correlation between the decrease in the rSO 2 and the percentage of change in the peak transcranial Doppler velocity in patients with contralateral carotid stenosis and occlusion. Levy and associates (17) have shown that, in patients undergoing tests for automatic defibrillator placement, EEG changes are correlated with changes in cerebral oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that a decrease in regional cerebral oxygen saturation (rSO 2 ) is a predictor of cerebral injury (16–20). The particular near‐infrared spectroscopy (NIRS) system used in our study monitors the critical balance between the rSO 2 and cerebral oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%